CD4+ T lymphocyte recovery in the modern antiretroviral therapy era: Toward a new threshold for defining immunological non-responders - Taramasso, Lucia; Labate, Laura; Briano, Federica; Brucci, Giorgia; Mora, Sara; Blanchi, Sabrina; Giacomini, Mauro; Bassetti, Matteo; Di Biagio, Antonio (Frontiers in Virology, 2023)
Introduction Despite the high level of efficacy of modern antiretroviral therapy (ART) in reducing HIV viremia and the control of viral replication, some people living with HIV (PLWH) do not recover their CD4+ T cell count. Methods To evaluate the frequency and predictive factors of discordant immune responses, we performed a retrospective cohort study of 324 antiretroviral-naïve PLWH who initiated first-line ART between 2008 and 2018 and maintained HIV RNA < 50 copies/ml during 36 months of follow-up. PLWH were defined as immunological non-responders (INRs) when CD4+ T cell count was < 20% compared with baseline (INR20%), or < 500 cells/mm3 (INR500) or < 200 cells/mm3 (INR200) at 36 months. Results The prevalence of INR20%, INR500, and INR200 was 12.5%, 34.6%, and 1.5%, respectively. After adjustment for possible confounders, CD4 nadir showed a significant association with all INR definitions, with lower values predicting INR500 (aOR 0.98, 95% CI 0.98–0.99, p < 0.001) and INR200 (aOR 0.98, 95% CI 0.95–1.01, p = 0.096). Moreover, a higher baseline CD4/CD8 ratio was inversely related to the probability of being INR500 (OR 0.03, 95% CI 0.01–0.12, p < 0.001) and INR200 (OR 0.002, 95% CI 18–7–67.72, p = 0.255). By contrast, INR20% had a higher CD4 nadir and CD4/CD8 ratio than other INRs, suggesting the identification of an heterogenous population with such definition. Discussion The present study highlights how INR200 has become rare in the contemporary ART era, and about one-third of PLWH meet the criteria for INR500. Overcoming the threshold of 500 CD4/mm3 could be an appropriate definition of immune response, in contrast with the older definitions of INR200 and INR20%. Early diagnosis and rapid treatment initiation, before CD4 counts and the CD4/CD8 ratio begin to decline, are critical for achieving an optimal immune response.